1995
DOI: 10.1084/jem.181.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of in vivo alloreactivity by inhibition of inducible nitric oxide synthase.

Abstract: Summs~The role of nitric oxide in the immune response to allogeneic tissue was explored in an in vivo cardiac transplant model in the rat. Nitric oxide production during organ rejection was demonstrated by elevations in systemic serum nitrite/nitrate levels and by electron paramagnetic resonance spectroscopy. Messenger RNA for the inducible nitric oxide synthase enzyme was detected in the rejecting aUografted heart, but not in the nonrejecting isografted heart. The enzyme was demonstrated to be biologically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(96 citation statements)
references
References 28 publications
1
90
0
5
Order By: Relevance
“…43 The cytokine and endotoxin upregulation of COX-2 and iNOS in various cells and tissues is suppressed by dexamethazone and by other immunosuppressive drugs such as cyclosporin A and FK506. 4,10,22,25,44 As mentioned previously, endothelial cell expression of COX-2 may be vasculoprotective by augmenting PGI 2 synthesis. 8 The finding of increased myocardial fibrosis in COX-2 knockout mice suggests that endocardial endothelial cell COX-2 may also be protective by augmenting PGI 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…43 The cytokine and endotoxin upregulation of COX-2 and iNOS in various cells and tissues is suppressed by dexamethazone and by other immunosuppressive drugs such as cyclosporin A and FK506. 4,10,22,25,44 As mentioned previously, endothelial cell expression of COX-2 may be vasculoprotective by augmenting PGI 2 synthesis. 8 The finding of increased myocardial fibrosis in COX-2 knockout mice suggests that endocardial endothelial cell COX-2 may also be protective by augmenting PGI 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Acute allograft rejection represents a typical Th1 response characterized by a predominant production of pro-inflammatory cytokines, IL-2, TNF-, and IFN-, with a low production of Th2 cytokines, IL-4, IL-10, and TGF- (Wu et al, 1992;Strom et al, 1996). Previous studies have also shown that production of NO represents one of the mechanisms participating in graft rejection (Worrall et al, 1995). Kinetics of allograft rejection and the fate of skin allografts correlated with the level of NO or its metabolites produced in the graft (Krulova et al, 2002) and the inhibition of NO production resulted in prolonged allograft survival (Worrall et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that production of NO represents one of the mechanisms participating in graft rejection (Worrall et al, 1995). Kinetics of allograft rejection and the fate of skin allografts correlated with the level of NO or its metabolites produced in the graft (Krulova et al, 2002) and the inhibition of NO production resulted in prolonged allograft survival (Worrall et al, 1995). Our results showed that CT20126 significantly suppressed the production of NO, TNF-, IL-1 , and IL-2 and failed to effectively inhibit IL-4 and IL-10 in the sponge matrix allograft model (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in a rat renal transplant model, liposomal clodronate administration 1 d posttransplantation, which depletes the majority of MΦ, reduces allograft damage (Jose et al, 2003), although liposomal clodronate also depletes other subsets of monocytes and DC thus complicating interpretation of the data. The production of iNOS in particular seems important for allograft rejection, as its neutralization prolongs cardiac allograft survival in mice (Roza et al, 2000;Worrall et al, 1995).…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%